2004
DOI: 10.1128/aem.70.9.5391-5397.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic Cyanobacteria onChara vulgarisAre the Main Contributors to N2Fixation in Rice Fields

Abstract: The distribution of nitrogenase activity in the rice-soil system and the possible contribution of epiphytic cyanobacteria on rice plants and other macrophytes to this activity were studied in two locations in the rice fields of Valencia, Spain, in two consecutive crop seasons. The largest proportion of photodependent N 2 fixation was associated with the macrophyte Chara vulgaris in both years and at both locations. The nitrogen fixation rate associated with Chara always represented more than 45% of the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The fact that we were unable to amplify cyanospecific nifH from RNA indicates that the cyanobacteria may be less active than heterotrophic diazotrops in this paddy field and that the input from the heterotrophic diazotrophic communities in the total nitrogen fixation budget might have been underestimated in previous studies. In accord, some recent studies indicate that the density and significance of cyanobacteria in rice paddy soil may have been overestimated when using culture-or microscopybased techniques (Ariosa et al 2004). A more detailed study should be undertaken to investigate the nitrogen fixation input from cyanobacteria and other potential diazotrophic members of the community.…”
Section: Discussionmentioning
confidence: 95%
“…The fact that we were unable to amplify cyanospecific nifH from RNA indicates that the cyanobacteria may be less active than heterotrophic diazotrops in this paddy field and that the input from the heterotrophic diazotrophic communities in the total nitrogen fixation budget might have been underestimated in previous studies. In accord, some recent studies indicate that the density and significance of cyanobacteria in rice paddy soil may have been overestimated when using culture-or microscopybased techniques (Ariosa et al 2004). A more detailed study should be undertaken to investigate the nitrogen fixation input from cyanobacteria and other potential diazotrophic members of the community.…”
Section: Discussionmentioning
confidence: 95%
“…, 1992). An association between extant Charales and epiphytic nitrogen‐fixing bacteria has also been reported (Ariosa et al. , 2004); however, SLs seem unable to stimulate bacterial growth (Soto et al.…”
Section: Discussionmentioning
confidence: 96%
“…Also, Ariosa et al . () found that cyanobacteria in the common rice weed Chara vulgaris L. significantly improved soil fertility through their capacity to fix nitrogen in the weed biomass. Eight studies (35%) demonstrated that weed biomass increased carbon inputs in the soil (e.g.…”
Section: Resultsmentioning
confidence: 99%